The moderating role of spirituality on quality of life and depression among adolescents with spina bifida. (2nd May 2020) - Taha, Asma A.; Eisen, Aaron M.; Abdul‐Rahman, Hana Q.; Zouros, Alexander; Norman, Sharon
Abstract: Aim: To investigate the relationships between spirituality, somatic symptom distress/severity, depressive symptoms and quality of life (QOL) for adolescents diagnosed with spina bifida (SB). Design: Exploratory, cross‐sectional design. Methods: Fifty‐eight adolescents with SB in southern California were recruited during routine visits to a multidisciplinary clinic at a healthcare university from January 2016–January 2017. Each adolescent completed a series of self‐report measures, including the System of Belief Inventory, Somatic Symptom Scale, Patient Health Questionnaire and Pediatric Quality of Life Inventory. Path analysis was performed to examine regression coefficients for each direct and indirect effect. Results: The mediation–moderation analysis showed that depressive symptoms fully mediated the relationship between symptom distress and QOL ( B = 0.029 [0.014], CI [0.007, 0.061]) and higher levels of spirituality moderated the relationship between depressive symptoms and QOL ( B = 0.052, p = .018). Spirituality was higher for adolescents with greater symptom severity; including shunt status Welch's F (1, 53.689) = 4.174, p = .046, level of lesion F (2, 57) = 3.382, p = .041, and ambulation status F (3, 57) = 2.920, p = .042. Conclusion: Adolescents with SB who had greater levels of symptom distress experienced significantly higher levels of depressive symptoms and a lower QOL. Contrary to our expectations, adolescents with greater levels of spirituality had a lower QOL when depressive symptoms were mild/moderate, but no differences were noted when depressive symptoms were severe. Impact: This study examined the relationship between spirituality and quality of life (QOL) in adolescents with spina bifida, who were experiencing different levels of depressive symptoms and symptom distress/severity. Depressive symptoms appeared to have a more profound effect on QOL than spirituality. Accordingly, we recommend that healthcare professionals actively screen for depressive symptoms when assessing these adolescents and their physical symptoms/distress levels. Abstract : 目的: 探讨脊柱裂(SB)青少年的精神状态、身体症状痛苦/严重性、抑郁症状与生活质量(QOL)的关系。 设计: 探索性的横断式设计。 方法: 从2016年1月至2017年1月, 招募58名患有脊柱裂的青少年前往南加州某医科大学的多学科诊所进行定期随访。每个青少年都完成了一系列自陈式测量, 包括信念系统调查表、身体症状量表、患者健康问卷和儿科生活质量调查表。并采用通径分析检查每种直接和间接影响的回归系数。 结果: 中介‐调节分析显示, 抑郁症状对于抑郁症状与生活质量的关系起到完全的中介作用( B = 0.029 [0.014], CI [0.007, 0.061]), 精神状态的程度越高, 对于抑郁症状与生活质量的关系越有调节作用( B = 0.052, p = .018)。症状越严重的青少年, 其精神状态分数越高;包括分流状态Welch's F (1, 53.689) = 4.174, p =0.046, 损伤程度 F (2, 57) = 3.382, p =0.041, 以及下床活动状态 F (3, 57) = 2.920, p =0.042。 结论: 患有脊柱裂青少年的症状困扰程度越大, 则抑郁症状程度越高, 生活质量越低。与我们的预期相反, 当抑郁症状为轻度/中度时, 精神状态更高的青少年的生活质量更低, 但当抑郁症状为重度时, 则没有发现到差异。 影响: 本研究探讨脊柱裂青少年的精神状态与生活质量的关系, 这些青少年具有不同程度的抑郁症状和症状痛苦/严重性。抑郁症状对生活质量的影响似乎比精神状态更加深远。因此, 我们建议医护人员在评估这些青少年及其身体症状/痛苦程度时应积极筛查抑郁症状。